2017
DOI: 10.9788/tp2017.3-19en
|View full text |Cite
|
Sign up to set email alerts
|

Violence in Intimate Relationship between Same-Sex Partners: Prevalence Study

Abstract: This study aimed to characterize the prevalence of violence in intimate relationships between same-sex partners in Portugal using the Revised Confl ict Tactics Scales. The study included 168 participants, mainly women (76.2%), who were between 18 and 35 years of age with an average age of 22.5 (SD = 3.79). In terms of perpetration, the results showed higher rates for psychological aggression (70.2% mild and 29.8% severe), physical abuse that leaves no sequelae (26.8% mild and 9.5% severe) and mild sexual coerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
2
4
1
2
Order By: Relevance
“…27, nº 1, p. 127-139 -March/2019 2005) showed that they are inferior to those of OSIPVs. These results contrast those found by Costa and colleagues (2011), in which SSPIV rates are higher than OSIPV rates, and by Santos and Caridade (2017), in which prevalence rates in SSIPV are alarming (perpetration rates of 92.3% and victimization rates of 91.7%). It is important to point out that there is no consensus in the literature about prevalence rates in SSIPV (Barret & Pierre, 2013).…”
Section: Género Y Violencia En La Intimidad Entre Personas Del Mismo contrasting
confidence: 82%
“…27, nº 1, p. 127-139 -March/2019 2005) showed that they are inferior to those of OSIPVs. These results contrast those found by Costa and colleagues (2011), in which SSPIV rates are higher than OSIPV rates, and by Santos and Caridade (2017), in which prevalence rates in SSIPV are alarming (perpetration rates of 92.3% and victimization rates of 91.7%). It is important to point out that there is no consensus in the literature about prevalence rates in SSIPV (Barret & Pierre, 2013).…”
Section: Género Y Violencia En La Intimidad Entre Personas Del Mismo contrasting
confidence: 82%
“…In this sense, seeking to understand the victim's reasons and the process inherent to the decision to remain in or leave an abusive relationship, is essential for the support provided to DV victims, as well as to mitigate the consequences/effects that may arise for their welfare. Although there are already some Portuguese studies documenting the disturbing indicators of DV among young people in Portugal (e.g., Caridade 2018;Guerreiro et al 2017;Machado et al 2010;Neves et al 2016;Santos and Caridade 2017), specific studies conducted with DV victims are scarce in the context of Portuguese reality. In addition, other Portuguese studies (e.g., Cerejo 2014;Pinto 2018) that have attempted to analyse the reasons for maintaining or leaving abusive relationships mainly focus on marital relationships.…”
Section: Research Aimmentioning
confidence: 99%
“…The results of this important Portuguese research revealed that violence in intimate relationships was a hidden reality, strongly conditioned by the dominant system of values, norms and social models, thus increasing a progressive interest on the part of the scientific community to explore this problem. Since then, several additional Portuguese (e.g., Machado et al 2010;Neves et al 2016;Santos and Caridade 2017) studies were developed, documenting the higher prevalence of dating violence (DV), and demonstrating that it is a widespread problem. Other international studies for self-protection and prevention of future violence (Caridade 2018).…”
Section: Introductionmentioning
confidence: 99%
“…La violencia de pareja puede definirse como aquellos actos violentos que se realizan de manera física, sexual y psicológica por la pareja (Longobardi & Badenes-Ribera, 2017). Se trata de un área temática dentro de las relaciones interpersonales, cuyo estudio inicia en los años setenta (González et al, 2016;Santos & Caridade, 2017) orientando su análisis, principalmente, en las parejas heterosexuales (Whitehead et al, 2020). Es así como la investigación de este fenómeno centrada en parejas del mismo sexo surge a finales de los años ochenta y principios de los noventa (Badenes-Ribera et al, 2016) como resultado de haberse considerado un problema de salud (Kubicek, 2018;Pagliaro et al, 2019;Santos & Caridade, 2017).…”
Section: Introductionunclassified
“…Se trata de un área temática dentro de las relaciones interpersonales, cuyo estudio inicia en los años setenta (González et al, 2016;Santos & Caridade, 2017) orientando su análisis, principalmente, en las parejas heterosexuales (Whitehead et al, 2020). Es así como la investigación de este fenómeno centrada en parejas del mismo sexo surge a finales de los años ochenta y principios de los noventa (Badenes-Ribera et al, 2016) como resultado de haberse considerado un problema de salud (Kubicek, 2018;Pagliaro et al, 2019;Santos & Caridade, 2017). Es probable que por ser un área joven de estudio En este contexto, es importante resaltar que el estudio de esta población presenta algunas dificultades para su análisis, siendo una de las principales el heterocentrismo (De Jesus, 2013), que puede manifestarse en diversas cuestiones como el prejuicio sexual; esta conducta puede evidenciarse por medio de un rechazo verbal, discriminación y ataques físicos, los cuales también pueden tener un impacto negativo en la salud mental (Gómez & Barrientos, 2012).…”
Section: Introductionunclassified